Assessment of Hydrogeochemisty and Evaluation of Groundwater Quality Feasibility Zones in Bhavani Taluk, Tamilnadu, India - J. Abdul Bari, M.Jamuna, (International Journal of Advanced Science and Technology, 2020)
Groundwater one of the prime source for domestic purposes in the area of BhavaniTaluk, Erode District, Tamilnadu, India. Erode district is one of the agricultural dominant district which lies in the North part of Tamilnadu. The groundwater samples from dug well and bore well were collected during two different monsoons like pre and post rainy seasons. The col-lected samples were assessed for its quality and suitability for drinking and irrigation purpose using geo-chemical process. A total of 46 sampling points were selected and the groundwater was extracted from different sampling locations of Erode district. The sampled groundwater were examined for cations, anions, potential of Hydrogen ion, Conductivity of water and sol-ids concentration. % of Sodium present in the sample were determined based on chemical data to find the suitability of water for agricultural purpose. Presence of Hydro geochemical facies were also identified by making use of piper trilinear diagram. The analyzed groundwa-ter parameters were tabulated and compared with drinking water standards formulated by World Health Organization (1994). Based on the result it was concluded that most of the lo-cations were within the limit which can be used for drinking purpose. Also, spatial distribu-tion map for the analyzed physical and chemical parameters were plotted with the help of ArcGIS.